COMPETITIVE SORPTION OF MULTIPLE COMPONENT HEAVY METALS FROM GOLD MINING LEACHATE ONTO LATERITE SOIL - A. Putthividhya (International Association of Lowland Technology, 2008)
It is important to understand the mechanisms of releasing of metal elements from mining industries in order to predict or estimate migration of these contaminants in the environment and initiate necessary policy for pollution control and prevention in groundwater aquifer systems. In this study, we focus particularly on assessing the competitive sorption characteristics of Pb, Zn, Ni, and Mn in batch equilibrium experiments using single and multiple metal solutions in natural laterite soil from the Northern Thailand. A series of batch tests was conducted to evaluate the effects of pH on sorption/desorption characteristics of metals and to estimate the sorption/desorption isotherms. Soil chemical processes were characterized using Linear, Langmuir, and Freundlich equations, and the results indicated that sorption isotherms were very well described by the Langmuir model. Pb had the greatest sorption capacity as estimated by the maximum sorption parameter (Qmax) of the Langmuir equation. Sorption characteristics were discovered to be dynamic processes, depending on interaction among multiple component heavy metals, soil properties, and concentrations of metals in the solution. Additionally, the impacts of variable water saturation on heavy metal migration were also explored by employing parameters obtained from previous experiments as input parameters in HYDRUS-2D model to simulate the migration of heavy metals through variable saturated porous media. The computer simulations revealed that the migration of the mixed contaminated plume was governed mainly by the mechanisms in unsaturated zone, rather than the hydraulic head gradient in the saturated zone. In addition, decreasing water contents resulted in higher retention time, promoted the late arrival of water fronts, and therefore could extend the contaminants’ lifetime in the system. Drier soil retarded transport of metals particularly in shallow unsaturated zone, leading to the possible pathway for the contaminants may get back in the hydrologic cycle via plant root uptake.